L’Angleterre et le Continent―Xe et début XIe siècles - Marthe Mensah (Anglophonia)
Relations between Anglo-Saxon England and the Continent were important in ways that affected several domains. Their influence can be observed in the political, legal, commercial, religious sectors as well as in the arts. The present article focuses mainly on the religious and artistic innovations that arose from such contacts. The major development of the 10th century was the monastic reform which was influenced by and indebted to contacts with the continent which are reflected in the Regularis Concordia, the manual of monastic usage to which every Anglo-Saxon monk was required to conform.This monastic reform was supported by the King and the alliance between King and Church helped further the development of artistic life in monastic scriptoria, in particular the creation of magnificent illuminated manuscripts, such as the Benedictional of Saint Aethelwold or the Harley Psalter inspired by continental models.Religious literature in the vernacular developed at the same time among which the best examples are the writings of Ælfric and Wulfstan who sometimes drew their inspiration from the Continent.